2010
DOI: 10.2519/jospt.2010.3185
|View full text |Cite
|
Sign up to set email alerts
|

Lower Extremity Kinematics of Females With Patellofemoral Pain Syndrome While Stair Stepping

Abstract: Study Design Cross-sectional case-control design. Background Although the etiology of patellofemoral pain syndrome (PFPS) is not completely understood, there is some evidence to suggest that hip position during weight-bearing activities contributes to the disorder. Objective To compare the knee and hip motions (and their coordination) during stair stepping in female athletes with and without PFPS. Methods Two groups of female recreational athletes, 1 group with PFPS (n = 10) and a control group without PFPS (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
1
7

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 27 publications
3
32
1
7
Order By: Relevance
“…This was the only kinematic variable for which findings were similar in both males and females. The present study also adds to the growing body of literature that has reported increased hip adduction during functional and sports activities in subjects with PFPS, 12,30,39,[45][46][47] and is in agreement with previous studies showing greater hip adduction in females compared to males. 15,52 Recently, a prospective study demonstrated that increased hip internal rotation during jump landing was a risk factor that predisposed individuals to PFPS.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This was the only kinematic variable for which findings were similar in both males and females. The present study also adds to the growing body of literature that has reported increased hip adduction during functional and sports activities in subjects with PFPS, 12,30,39,[45][46][47] and is in agreement with previous studies showing greater hip adduction in females compared to males. 15,52 Recently, a prospective study demonstrated that increased hip internal rotation during jump landing was a risk factor that predisposed individuals to PFPS.…”
Section: Discussionsupporting
confidence: 81%
“…However, the findings of these studies have been inconsistent. In the frontal plane, some studies have reported increased hip adduction 12,30,39,[45][46][47] and others have not. 4,11,42 It is possible that hip adduction may be the result of adduction of the femur relative to the pelvis, the pelvis dropping on the contralateral side, or a combination of both.…”
Section: T T Conclusionmentioning
confidence: 99%
“…Optou-se neste estudo por avaliar o ângulo de projeção no plano frontal do joelho durante step down em pacientes com SDP por ser uma atividade que exige controle do membro inferior para evitar valgo excessivo (65,70,88,89) . Além disso, ainda são escassos os estudos que avaliam a influência da força dos estabilizadores do quadril e tronco no valgo dinâmico do joelho em pacientes com SDP e controles.…”
Section: Justificativaunclassified
“…Estudos avaliando a biomecânica do quadril durante atividades funcionais encontraram que mulheres com SDP tem maior pico de rotação medial do quadril durante corrida, descida de escada e aterrissagem do salto em relação ao grupo controle, não havendo diferenças quanto à adução do quadril (63) . Enquanto Willson e Davis (28) relatam maior adução do quadril durante salto, corrida e agachamento unipodal, Bolgla et al (9) não encontraram diferenças na rotação medial e adução do quadril durante descida de escada e McKenzie et al (65) relata que mulheres com SDP tem maior adução e rotação medial de quadril e pé rodado internamente durante descida de escada.…”
Section: âNgulo De Projeção No Plano Frontalunclassified
See 1 more Smart Citation